ANALISIS TOKSIKOLOGI FORENSIK : KASUS KEMATIAN AKIBAT PENGGUNAAN PROPOFOL - Nandita, Putu Nandya (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 9 No 2 (2019): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2019.v09.i02.p01, 2019)
Some newspapers (mostly forensics) report cases of abuse, accidental overdoses or criminal purposes with propofol. Propofol is a drug that can reduce anxiety and stress, leading to relaxation and sleep or loss of consciousness. Suicides and intentional and unintentional killings related to the use of propofol have been widely reported. A number of analytical methods have been used to detect and measure the concentration of propofol in biological specimens. Forensic toxicology analysis of death cases related to the use of propofol is carried out from the process of preparing samples (biological specimens), conducting screening tests, ascertainment tests, determination, and interpretation of data.